Do community level interventions work in the same way on incidence and longitudinal prevalence of diarrhoea among under five children in rural and urban slum settings? Insights from Stop Diarrhoea Initiative in India - Farhad Ali; Om Prakash Singh; Abhik Dutta; Mahendra Bhushan Upadhyay; Debashmita Bhaumik (Journal of Global Health Reports)
# Background